2022
DOI: 10.1039/d2ob01386j
|View full text |Cite
|
Sign up to set email alerts
|

Deracemization of racemic alcohols combining photooxidation and biocatalytic reduction

Abstract: We described a cascade reaction for deracemization of racemic alcohols combing photooxidation and enzymatic reduction under mild condition without the isolation of intermediate ketones. By using different ketoreductases, a variety...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Furthermore, ( R )- 3ba was readily converted to ( S )- 3ba with an entirely reverse chirality under standard photoenzymatic conditions (Scheme e). These results ruled out the possibility of a photocatalytic oxidation/enzymatic reduction mechanism for the deracemization of rac - 3ba . The synthetic importance of this amino alcohol motif was emphasized by the reaction of ( S )- 3ba and 1,1′-carbonyldiimidazole ( 5 ), and the oxazolidinone product 6 can be easily produced in 99% yield and >99% ee (Scheme f).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ( R )- 3ba was readily converted to ( S )- 3ba with an entirely reverse chirality under standard photoenzymatic conditions (Scheme e). These results ruled out the possibility of a photocatalytic oxidation/enzymatic reduction mechanism for the deracemization of rac - 3ba . The synthetic importance of this amino alcohol motif was emphasized by the reaction of ( S )- 3ba and 1,1′-carbonyldiimidazole ( 5 ), and the oxazolidinone product 6 can be easily produced in 99% yield and >99% ee (Scheme f).…”
Section: Resultsmentioning
confidence: 99%
“…Die Autoren zitierten weitere Referenzen innerhalb der Hintergrundinformationen [56–108] . Ablagenummern: (https://www.ccdc.cam.ac.uk/services/structures?id=doi:10.1002/anie.202402885) 2313487 (für 2‐Amino‐5‐mesityl‐3‐methylpyridin), 2313446 (für 1‐AlPh 2 ), 2313488 (für 2‐AlMe 2 ), 2313489 (für 2‐AlEt 2 ), 2313490 (für 2‐Al i Bu 2 ), 2313491 (für 2‐Al t Bu 2 ), 2313492 (für 2‐AlPh 2 ), 2313493 (für 2‐AlCl 2 ), 2313485 (für 2‐Al(CH=CH 2 ) 2 ), 2313494 (für 2‐Al(C≡C‐TMS) 2 ), 2313495 (für 3‐AlMe 2 ), 2313496 (für 3‐AlPh 2 ) enthält zusätzliche kristallographische Daten für diesen Artikel.…”
Section: Hintergrundinformationenunclassified
“…Until now, only one example of a cascade reaction for the deracemization of racemic alcohols combining photoinduced oxidation and enzymatic reduction mediated by whole-cells containing (R)-selective KtCR or (S)-selective RasADH has been reported (Scheme 1G). 17 However, a photooxidation step catalyzed by SAS in water with supplemental acetonitrile (30%, v/v) furnished ketones in mostly nonquantitative yield (53− 97%), which can be expected to clearly impact the % ee-values of the desired alcohols if the reactions were conducted in a one-pot manner. To our surprise, the authors reported enantiomeric excesses for the obtained products with values in the 95−99% range, which does not match the obtained results of the photooxidation step, and suggests a two-pot reaction sequence carried out with indirect separation of the unreacted racemic alcohols.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In turn, direct photobiocatalytic deracemization of sec -alcohols toward enantiopure alcohols is still in its infancy. Until now, only one example of a cascade reaction for the deracemization of racemic alcohols combining photoinduced oxidation and enzymatic reduction mediated by whole-cells containing ( R )-selective KtCR or ( S )-selective RasADH has been reported (Scheme G) . However, a photooxidation step catalyzed by SAS in water with supplemental acetonitrile (30%, v/v) furnished ketones in mostly nonquantitative yield (53–97%), which can be expected to clearly impact the % ee-values of the desired alcohols if the reactions were conducted in a one-pot manner.…”
Section: Introductionmentioning
confidence: 99%